REVITALISASI TATA KELOLA DAN PERENCANAAN USAHA BUMDES DENGAN BISNIS MODEL CANVAS DI KECAMATAN NUSALAUT KABUPATEN MALUKU TENGAH - Meidylisa Patty; Angel Merlyn Pattimahu; Ennis Sarenah Kriekhoff; Audrey Leiwakabessy; Harry Anthony Pierre Sitaniapessy; Trudy Mariona Nussy (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
This community service program aimed to strengthen the capacity of Village-Owned Enterprises (BUMDesa) managers in governance and business planning in Nusalaut District, Central Maluku Regency. The main challenges faced by BUMDesa in island areas are not related to legal status, but rather to weak governance practices, administrative management, and limited business planning capacity. The program employed a participatory approach through lectures, interactive discussions, and hands-on training using the Business Model Canvas (BMC). Program effectiveness was evaluated through pre-test and post-test assessments. The results indicate a significant improvement in participants’ understanding of governance principles, business planning, and business model mapping based on local potential, particularly in the fisheries sector as a pillar of village food security. The activity also fostered awareness of the importance of inter-village collaboration among BUMDesa in island contexts. Overall, this program contributes to strengthening the institutional and managerial capacity of BUMDesa in a sustainable manner.